Photovoltaic Array Maximum Power Point Tracking Based on Improved Method - Jia Cunliang; Yanxiong Wang; Zerong Wang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
At present, a good deal of methods for the Maximum Power Point Tracking (MPPT) has been used in engineering applications. However, Matlab simulation proved that they were difficult to harmonize the stability and speed ability of system. In addition, in order to maximize the use of PV panels ‘power, the paper focused on aneonatalalgorithm for Maximum Power Point Tracking (MPPT). Based on the algorithm, this paper designed an improved and feasible variable step perturbation and observation method which well alleviated the conflict that the maximum power point tracking could not take into account the stability and speed of response efficiently.